Energy basal levels and allocation among lipids, proteins, and carbohydrates in Enchytraeus albidus: changes related to exposure to Cu salt and Cu nanoparticles - Amorim, Mónica J. B. (2019)
Energy intake and allocation are mainly used to maintain body functions, such as locomotion, growth, and reproductive output. It has been observed that environmental pollutants can affect the energy allocation either due to a cost of handling toxicants or because the toxicant interacts with the storage processes within the organisms. Less than a handful of studies are available reporting the effect of toxicants on energy reserves in enchytraeids and no studies have dealt with the influence of nanomaterials. The present paper shows results on the basal energy reserves (lipids, carbohydrates, and proteins) in Enchytraeus albidus and the influence of copper (Cu) salt and Cu nanoparticles on these reserves for two exposure durations. The energy allocation levels follow what has been reported for other worm species, although lower carbohydrate levels were observed. There were clear differences between worms exposed to control soils and those exposed to Cu for 3 weeks, but no difference after 6 weeks exposure. There was no apparent difference between the impacts of the two Cu exposure forms.